2019
DOI: 10.21608/bvmj.2019.120664
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of hygienic and nutritive quality of retailed minced meat in Egypt

Abstract: The study was conducted on ninety fresh, chilled and frozen minced meat to determine their bacterial and nutritional quality and to be screened for meat-borne pathogens in the Menofiya governorate. Statistically, the findings of Aerobic mesophilic, coliform, Staphylococci, and Staphylococcus aureus counts were not significantly different (P >0.05) between the three meat types. Compared to the Egyptian organization standards (EOS), 82.2 % of minced meat had unacceptable Aerobic mesophilic counts, while 79% show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 20 publications
0
0
0
Order By: Relevance
“…The reduction of peroxide values might be attributed to the phenols and flavonoids of CGE that have antioxidant activity. This agrees with several reports that showed that Cassia glauca has to be considered an effective antioxidant and a rich source of phenols and flavonoids, which possess antioxidant activity [16,42]. Therefore, the incorporation of CGE in minced beef inhibits lipid oxidation.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The reduction of peroxide values might be attributed to the phenols and flavonoids of CGE that have antioxidant activity. This agrees with several reports that showed that Cassia glauca has to be considered an effective antioxidant and a rich source of phenols and flavonoids, which possess antioxidant activity [16,42]. Therefore, the incorporation of CGE in minced beef inhibits lipid oxidation.…”
Section: Discussionsupporting
confidence: 92%
“…Consequently, it extends the shelf life and improves the quality of the minced beef. According to the permissible limits recorded by EOS [42], which stated that TABC should not exceed (6 log10 CFU/g), the control group exceeded the acceptable level by day 6 of storage compared to the minced meat samples treated with 0.25%, 0.5%, and 1%, which became unacceptable after 9, 12, and 15 days of storage at 3 ± 1 • C, respectively. Our results showed that CGE positively impacted the total aerobic plate count by increasing the CGE in minced meat from 0.25% to 0.5% and 1% and increasing the shelf life of minced meat from 6 to 9, 12, and 15 days, respectively.…”
Section: Discussionmentioning
confidence: 99%